Seroprevalence of Human Papillomavirus Types 6, 11, 16 and 18 in Chinese Women - Ji Jia; Sun Hai-Kui; Smith Jennifer S; Wang He; Esser Mark T; Hu Shangying; Pretorius Robert G; Chen Wen; Belinson Jerome L; Qiao You-Lin (BMC Infectious Diseases, 2012)
Abstract Background Human papillomavirus (HPV) seroprevalence data have not previously been reported for different geographical regions of China. This study investigated the cross-sectional seroprevalence of antibodies to HPV 6, 11, 16, and 18 virus-like particles in Chinese women. Methods Population-based samples of women were enrolled from 2006 to 2007 in 3 rural and 2 urban areas of China. Each consenting woman completed a questionnaire and provided a blood sample. Serum antibodies were detected using a competitive Luminex immunoassay that measures antibodies to type-specific, neutralizing epitopes on the virus-like particles. Results A total of 4,731 women (median age 35, age range 14-54) were included, of which 4,211 were sexually active women (median age 37) and 520 virgins (median age 18). Low risk HPV 6 was the most common serotype detected (7.3%), followed by HPV 16 (5.6%), HPV 11 (2.9%), and HPV 18 (1.9%). Overall HPV seroprevalence to any type was significantly higher among sexually active women (15.8%) than virgins (2.5%) (P = 0.005). Overall seroprevalence among sexually active women gradually increased with age. Women from rural regions had significantly lower overall seroprevalence (Odds Ratio (OR) = 0.7; 95% CI: 0.6-0.9, versus metropolitan regions, P < 0.001). With increasing number of sexual partners, women were at higher risk of seropositivity of any type (OR = 2.6; 95% CI: 1.7-3.9 for > = 4 partners versus 1 partner, P < 0.001). Wives were at higher risk of seropositivity for HPV 16/18/6/11 when reporting having a husband who had an extramarital sexual relationship (OR = 2.0; 95% CI: 1.6-2.5, versus those whose husbands having no such relationship, P < 0.001). There was a strong association between HPV 16 seropositivity and presence of high-grade cervical lesions (OR = 6.5; 95% CI: 3.7-11.4, versus normal cervix, P < 0.001). Conclusions HPV seroprevalence differed significantly by age, geography, and sexual behavior within China, which all should be considered when implementing an optimal prophylactic HPV vaccination program in China.